Beyond the Common Issues: Students' Perspective on Participation in Online Education - Sardar Shareef; Hozan Latif Rauf; Nizar Najim Othman (EDUTEC : Journal of Education And Technology, 2024)
The recent outbreak of the Coronavirus pandemic has increased the gaps in the education sector globally, changing the common route of face-to-face education to a virtual one. While this model is not free of shortages and challenges, documenting the literature illustrated remarkable tangible obstacles. Unfortunately, there is little in-depth research on students' points of view on the intangible struggles of online education, while intangible issues have been overlooked in developing countries such as Iraq. Therefore, this study aims to understand the unspoken problems that challenge students' participation in online courses. This qualitative study provides in-depth interviews with university students, more specifically architectural students, who participated in the online classes from 2019 to 2021 that online teaching was compulsory at the beginning and blended education last year. Realizing the phenomenon of low performance or not participating in the online lectures from the active students' side. As a result, the respondents show that despite providing all access to online lectures in architectural education, many obstacles faced the students. This research, initially focused on the intricate dynamics of educational reform in the Middle-east, offers valuable insights for the global higher education community, shedding light on universal challenges and innovative solutions that are applicable across various educational landscapes.